المهارات المهنية للمراجعين الداخليين وأثرها في تطبيق مبادئ حوكمة الشركات: دراسة ميدانية في البنوك الإسلامية بالجمهورية اليمنية - الريمي، عبدالله حسن Alraymi, Abdullah Hassan (جامعة العلوم والتكنولوجيا, 2018)
هدفت الدراسة إلى معرفة المهارات المهنية للمراجعين الداخليين وأثرها في تطبيق مبادئ حكومة الشركات بالبنوك الإسلامية اليمنية، وذلك باستخدام المنهج الوصفي التحليلي، وقد استخدم الباحث أسلوب الحصر الشامل لجمع البيانات، ووزع 70 استبيان لجميع المراجعين الداخليين في البنوك الإسلامية، ومفتشي البنك المركزي اليمني بصنعاء، استرجع منها 63 استبيان كان جميعها صالح للتحليل، وقد توصلت الدراسة إلى وجود أثر ذي دلالة معنوية للمهارات المهنية في تطبيق مبادئ حكومة الشركات بالبنوك الإسلامية اليمنية، كما توصلت إلى توافر ممارسات تطبيق مبادئ الحكومة، وكذا المهارات المهنية اللازمة لتطبيقها في البنوك الإسلامية اليمنية مع ظهور بعض مواطن الضعف والقصور، وقد أوصت الدراسة بضرورة الاهتمام بتطبيق مبادئ حكومة الشركات في البنوك الإسلامية، والإشراف المباشر من قبل مجالس الإدارات على وظيفة المراجعة الداخلية، وكذلك إشراك موظفي المراجعة الداخلية في الدورات التدريبية، والمؤتمرات، والندوات المرتبطة بالمراجعة الداخلية وحكومة الشركات، بالإضافة إلى توفير نسخ مطبوعة من معايير المراجعة الداخلية الدولية، ومبادئ حكومة الشركات، والتشريعات المصرفية المحلية والدولية.
This study aimed at identifying the professional skills of the internal auditors and the impact of these skills on the implementation of corporate governance principles in the Yemeni Islamic banks. The analytical descriptive method was adopted. To collect the required data, the census survey was used and 70 questionnaires were distributed to all the internal auditors in the Islamic banks and the inspectors of the Central Bank of Yemen in Sana'a. Sixty-three questionnaires were collected and all were valid for analysis. The results of the study revealed that the professional skills had a significant impact on the implementation of corporate governance principles in the Yemeni Islamic banks. The results also showed that the Islamic banks apply to some extent the governance principles as well as the professional skills in the Islamic banks. The study recommended that it is important for the Islamic banks to implement the corporate governance principles and the internal audit function should be supervised directly by the boards of directors. The study also recommended that the internal audit staff should be involved in training courses, conferences, seminars related to internal auditing and corporate governance as well as the international standards of internal audit and corporate governance principles. Additionally, copies of the international internal audit standards and local and international banking legislations should be provi
Keywords: المراجعة الداخلية -- المراجعين الداخليين -- المهارات المهنية -- حوكمة الشركات -- البنوك الإسلامية -- اليمن